2001
DOI: 10.1136/heart.85.5.561
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular stents in the management of coarctation of the aorta in the adolescent and adult: one year follow up

Abstract: Objectives-To test the hypothesis that endovascular stents used with dilation of coarctation of the aorta (CoA) improve late outcomes. Balloon dilation for CoA has been limited by concerns over the risk for acute dissection, late restenosis, or aneurysm formation. Design-All patients seen with CoA between November 1994 and September 1997 underwent attempted stent implantation. Follow up was obtained for all patients and a subgroup (n = 18) had repeat catheterisation at a mean (SD) of 1.3 (0.5) years to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
119
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(135 citation statements)
references
References 33 publications
13
119
2
1
Order By: Relevance
“…Mean gradient at catheterisation was 71.7 ± 28.6 mm hg and mean gradient post procedure was 3.6 ± 4.4 mmhg. In our literature search, similar encouraging results have been reported in other countries -Harrison et al found that the mean peak pressure gradient of 46 ± 20 mmHg at baseline was reduced to a mean gradient of 4 ± 6 (range 0-26) mmHg at follow-up 1-3 years later (6) . In Hamdan et al's study the peak systolic pressure gradient measured at catheterisation decreased from 32 ± 12 mmHg to 4 ± 11 mmHg, while the echocardiographic Doppler gradient decreased from 51 ± 26 mmHg to 13 ± 11 mmHg at follow-up , (7) .…”
Section: Methodssupporting
confidence: 89%
“…Mean gradient at catheterisation was 71.7 ± 28.6 mm hg and mean gradient post procedure was 3.6 ± 4.4 mmhg. In our literature search, similar encouraging results have been reported in other countries -Harrison et al found that the mean peak pressure gradient of 46 ± 20 mmHg at baseline was reduced to a mean gradient of 4 ± 6 (range 0-26) mmHg at follow-up 1-3 years later (6) . In Hamdan et al's study the peak systolic pressure gradient measured at catheterisation decreased from 32 ± 12 mmHg to 4 ± 11 mmHg, while the echocardiographic Doppler gradient decreased from 51 ± 26 mmHg to 13 ± 11 mmHg at follow-up , (7) .…”
Section: Methodssupporting
confidence: 89%
“…This falls into a mid-range when compared with other studies of coarctation stenting (56%-88%). 5,[8][9][10][11][12][13] As this study demonstrated, complications today are uncommon and meticulous attention to detail will continue to keep rates low. We do not support a standard dose of heparin and default to a weight-based heparin load followed by activated clotting time monitoring, and we do not use the brachial artery for a second arterial access because a randomized angioplasty trial has identified brachial access with the highest rate of complications versus radial with the lowest and femoral arterial next.…”
Section: See Article By Kische Et Almentioning
confidence: 83%
“…3 Several surgical approaches have evolved during the years, with percutaneous treatment options only becoming available in the 1980s, first with balloon angioplasty and balloon expandable stent implantation in the late 1990s. 4,5 Although clinical acceptance of percutaneous approaches was initially slow, improved techniques, operator experience, and balloon and stent technology have resulted in an enhanced clinical acceptance with improved safety profiles and success rates, although not without controversy. 6 There remains a scarcity, however, of long-term follow-up studies after endovascular repair in regards to the development of aneurysm formation, recurrent obstruction, and general cardiovascular mortality and morbidity.…”
mentioning
confidence: 99%
“…The study confirmed the hypothesis but went on to mention that approximately one-fifth of the patients who underwent angiography came back with aortic dilatation. 4 …”
Section: Discussionmentioning
confidence: 99%